Abortion associated with Brucella abortus strain RB51 vaccination during gestation in a dairy cow immunized with strain 19 as a calf - Cabaña, Enzo (2025)
Bovine brucellosis, caused by Brucella abortus, is a zoonotic disease that leads to abortions in cattle and poses a public health risk. Vaccination with live attenuated strains, including S19 and RB51, is part of control programs. Both vaccines are recommended in calves, and RB51 is used for adult cattle in endemic herds due to its lack of interference with serological diagnosis. Experimental studies suggest prior S19 vaccination may protect against abortion following RB51 administration during gestation. Here, we report a case of abortion in a dairy cow, sero-negative to Brucella diagnostic assays, previously vaccinated with S19 as a calf and subsequently immunized with RB51 during the first trimester of pregnancy. The cow belongs to a herd infected with B. abortus five years ago, where a plan for eradication of brucellosis is being implemented. The abortion occurred at seven months of gestation, five months after RB51 immunization. Necropsy and histopathology of the fetus revealed systemic lesions consistent with brucellosis. Brucella was isolated from fetal lung and abomasal fluid, and PCR confirmed the isolate as RB51. Serological tests performed on the cow were negative, highlighting the diagnostic limitations in RB51-vaccinated animals. This case represents the first documented abortion caused by RB51 in a cow previously immunized with S19. These findings support the recommendation to avoid RB51 vaccination in pregnant cows to prevent abortion and potential zoonotic transmission.